Psychological Capital as A Mediator of Taqwa (Islamic Piety) on The Well-Being of Working Mothers with Special Needs Children - Ikhwanisifa, Ikhwanisifa; Susanti, Rita; Damayanti, Indah (International Journal of Islamic Educational Psychology, 2025)
Mothers with special needs children carry many burdens in raising their children, such as psychological, emotional, and family burdens. The burdens felt will certainly affect the mothers' happiness. Several factors can enhance the happiness of mothers with special needs children, including taqwa and psychological capital. This study examined psychological capital as a mediator of taqwa on the well-being of working mothers with special needs children in Pekanbaru, Riau.  This research was conducted on working mothers with special needs children, involving 145 respondents. Path analysis employed JASP 0.18.3 assistance. The results indicated that taqwa and psychological capital directly and significantly affected the well-being of working mothers with special needs children. However, psychological capital cannot be considered a perfect mediating variable (z=0.662; p < 0.001). This study implies that taqwa and psychological capital are significant in enhancing well-being; thus, it is recommended that both variables be improved among working mothers with special needs children to enhance their well-being.